Integrating Podcasting to Enhance Public Speaking and Pedagogical Excellence of Preservice Language Communication Teachers in Ilorin Public Universities - Usman Abubakar; Aderonke Kofo Soetan; Hussaini Ibrahim (WISE Pendidikan Indonesia, 2025)
Public speaking is an essential skill for educators, yet many preservice language teachers struggle with anxiety, limited practice opportunities, and inadequate training. This study explores the integration of podcasting as a technology-enhanced tool to improve public speaking proficiency and pedagogical excellence among preservice language teachers in public universities in Ilorin, Nigeria. A descriptive survey research design was employed, involving 457 participants, with data collected through a validated questionnaire and analyzed using descriptive statistics. The results reveal generally positive attitudes towards podcasting as an educational tool, with participants reporting improvements in speech organization, audience engagement, and independent learning skills. However, challenges such as technical barriers, insufficient internet connectivity, and lack of training persist. Despite these limitations, podcasting demonstrated significant potential in reducing speaking anxiety, fostering digital literacy, and enhancing critical thinking skills. This study highlights podcasting as a flexible and innovative medium for addressing traditional challenges in public speaking education. It contributes to the growing body of knowledge on e-learning and educational media by demonstrating how podcasting can bridge the gap between theoretical knowledge and practical application, offering a scalable and inclusive solution for teacher education. Future research should explore long-term impacts and cross-cultural comparisons to further validate these findings.